2012
DOI: 10.1021/cm203754a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Pore Size of Ink-Bottle Mesopores by Atomic Layer Deposition

Abstract: Atomic layer deposition is demonstrated to be greatly suitable to tune the pore size of ink-bottle mesopores at the atomic level. This is confirmed by quantitative electron tomography, which enables a direct and local 3D characterization of an ultrathin HfO2 coating deposited in the mesopores of a thin titania film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…The porous silica film has mesopores of the order of several nanometers. As has already been shown in literature, 21,34,60 these structures can be either conformally coated with ALD or the pores can be sealed. To ensure a large enough penetration depth for the x-rays, and incident angle of 1 was chosen for these experiments, instead of the previously used incident angle of 0.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The porous silica film has mesopores of the order of several nanometers. As has already been shown in literature, 21,34,60 these structures can be either conformally coated with ALD or the pores can be sealed. To ensure a large enough penetration depth for the x-rays, and incident angle of 1 was chosen for these experiments, instead of the previously used incident angle of 0.…”
mentioning
confidence: 82%
“…This was shown for the growth of TiO 2 in porous silica films. [32][33][34] The penetration depth of x-rays for energies typically used during XRF is on the order of microns. If the thickness of the studied layers is larger than a few 100 nm, the reabsorption of fluorescent x-rays needs to be taken into account, since this changes the relation between the intensity of the fluorescent x-rays and the amount of material.…”
Section: Elemental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Only few studies have reported efforts to characterize ALD deposition in sub-10 nm pores. George and co-workers investigated ALD of Al 2 O 3 , TiO 2 and SiO 2 in ~5 nm tubular alumina membranes by deriving the pore diameter after each ALD half cycle from in situ N 2 conduction measurements. 13,14 This valuable in situ approach is, however, only applicable to membrane supports.…”
Section: Introductionmentioning
confidence: 99%
“…This thin film growth method is known to produce thin, conformal coatings with thickness control down to the atomic level, and has been proven successful for the synthesis and functionalization of nanostructured and highly porous materials. [12][13][14][15][16] Several authors have reported the ALD-based synthesis of TiO 2 nanotubes by using anodic alumina as a template. [17][18][19] Here, we use multi-walled carbon nanotubes (MWCNTs) as sacrificial templates.…”
Section: Introductionmentioning
confidence: 99%